Correlation Study: The Relationship Between Emotional Intelligence and Social Attitude of Elementary School Students - Ramdan, Muhamad; Syarida, Sherly; Faturrahman, Arya; Nugraha, Syalaisha Salsabila; Giwangsa, Sendi Fauzi (Universitas Trunojoyo Madura, 2024)
Emotional intelligence is an aspect of intelligence that needs to be nurtured in students to help direct their emotional lives more effectively. In elementary school, social attitudes are important to develop, one of which can be achieved through good parenting practices that foster positive emotions and empathy in children. At this stage, social attitudes begin to form as children's psychological conditions are influenced by their social environment and personal adjustment.This study aims to examine the relationship between emotional intelligence and social attitudes. The research method used is a correlational study. The results indicate a significant relationship between emotional intelligence and social attitudes. The emotional intelligence level of students at SDN 134 Panorama falls into the